2007
DOI: 10.1007/s11259-007-9021-y
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive dogs are characterized by low omega-3 polyunsaturated fatty acid status

Abstract: Canine aggressive behaviour is one of the most common problems being reported by dog owners. However, the biochemical basis of this phenomenon remains unclear. In humans, alterations in omega-3 plasma polyunsatured fatty acids and elevated omega6/omega-3 ratio have been linked to behavioural alterations, including aggression. Thus far, however, the relationship between plasma polyunsatured fatty acid status and aggression has not been investigated in the dog. In the present study we sought to investigate wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 20 publications
(16 reference statements)
0
20
1
1
Order By: Relevance
“…These studies have found increased aggressive behaviors with both omega-3 PUFA deficient (Demar et al, 2006) and high-omega-6 PUFA (Raygada, Cho, & Hilakivi-Clarke, 1998) intake, although depressive behaviors were increased on the omega-3 deficient diet and decreased on the elevated omega-6 diet. One study in dogs (Re, Zanoletti, & Emanuele, 2008) found that aggressive dogs were differentiable from normal animals by low DHA but not EPA levels, in contrast to our findings; however, they measured phospholipid rather than total plasma omega-3 PUFAs, and effects of substance use were not studied in the animal context.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies have found increased aggressive behaviors with both omega-3 PUFA deficient (Demar et al, 2006) and high-omega-6 PUFA (Raygada, Cho, & Hilakivi-Clarke, 1998) intake, although depressive behaviors were increased on the omega-3 deficient diet and decreased on the elevated omega-6 diet. One study in dogs (Re, Zanoletti, & Emanuele, 2008) found that aggressive dogs were differentiable from normal animals by low DHA but not EPA levels, in contrast to our findings; however, they measured phospholipid rather than total plasma omega-3 PUFAs, and effects of substance use were not studied in the animal context.…”
Section: Discussioncontrasting
confidence: 99%
“…Lower LC n -3 levels are associated with aggression, (54) with poor affective regulation and impulse control (55), and with increased rejection of unfair offers in a neuro-economic task (56). Rodent models implicate low LC n -3 levels in increased aggression, particular in settings of increased stress (57, 58); and even aggression in German Shepherd dogs is associated with low DHA levels (59). …”
mentioning
confidence: 99%
“…Thus, a Wi-Fi range extender was used to completely cover the distance between those boxes and the Wi-Fi station. Many studies have been performed to validate the usefulness of small, lightweight, motionsensing accelerometers for pets 44 and humans [46][47][48][49][50][51][52][53][54] . The sensor used in this clinical evaluation presents some limitations with respect to the goldstandard method of using a video camera 55,56 , such as a lack of specificity in distinguishing rest activity from sleep and general motion from an anxiety-related one.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PUFA have been show to modulate behavioral symptoms in attention-deficit hyperactivity disorder (ADHD) patients and in aggressive dogs 43 . These dogs had lower docosahexaenoic acid (DHA) levels than normal, as well as a higher omega-6:omega-3 ratio 44,45 . …”
mentioning
confidence: 99%